Sadik Transform, The Generalization Of All The Transform Who’s Kernal Is Of Exponential Form With The Application In Differential Equation With Variable Coefficients - et.al, Mohmed Zafar Saber, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In This Paper We Have Tried To Produce General Form Of All The Integral Transforms Whose Kernel Is Of Exponential Form By Changing Different Values Of Alfa And Beta In Sadik Transform, We Have Produces General Form Of Sadik Transform Over Laplace Transform, Sumudu Transform, Elzaki Transform, Kamal Transform, Abood Transform, Tarig Transform, Mohand Transform Etc. Also We Have Solved Differential Equation Of Order One With Variable Coefficients By Sadik Transform And Analysis Which Transform Can Solve This Differential Equation For Particular Value Of Coefficients A And B. Keywords: The Sadik Transform, Laplace Transform, Sumudu Transform, Elzaki Transform, Kamal Transform, Abood Transform, Tarig Transform, Mohand Transform Etc, Differential Equation With Variable Coefficients.